2015
DOI: 10.1155/2015/952395
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast DNA Variations in Wild Brassicas and Their Implication in Breeding and Population Genetics Studies

Abstract: Evaluation of chloroplast DNA (cpDNA) diversity in wild relatives of crop brassicas is important for characterization of cytoplasm and also for population genetics/phylogeographic analyses. The former is useful for breeding programs involving wide hybridization and synthesis of alloplasmic lines, while the latter is important for formulating conservation strategies. Therefore, PCR-RFLP (Polymerase Chain Reaction-Restriction Fragment Length Polymorphism) technique was applied to study cpDNA diversity in 14 wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This postulation was supported by Yang et al, (2002), who reported that the chloroplast noncoding region between trnD & trnT and that between trnT & trnF are useful for studying the interspecific relationships among angiosperms. The achieved results for the cpDNA markers reveal the intraspecific polymorphisms in Egyptian wild B. nigra taxa, is a useful tool for conservation and as marker assisted Brassica breeding programs, as reported by Sarin et al (2015). The detected low divergence between the two forms of var.…”
Section: Discussionmentioning
confidence: 54%
“…This postulation was supported by Yang et al, (2002), who reported that the chloroplast noncoding region between trnD & trnT and that between trnT & trnF are useful for studying the interspecific relationships among angiosperms. The achieved results for the cpDNA markers reveal the intraspecific polymorphisms in Egyptian wild B. nigra taxa, is a useful tool for conservation and as marker assisted Brassica breeding programs, as reported by Sarin et al (2015). The detected low divergence between the two forms of var.…”
Section: Discussionmentioning
confidence: 54%
“…Studies on cpDNA diversity are also essential for population genetics and phylogeographic analysis of rare, endemic and endangered varieties [20]. Additionally, cpDNA's conserved structure and low nucleotide replacement rate are crucial for phylogenetic investigations [21].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal inheritance is essential for hybrid breeding programs and mitochondrial and chloroplast genomes. CMS is a maternally inherited trait in flowering plants that cannot produce functional pollen [3]. Several cellular metabolic processes mandatory for higher plants, such as ATP production by oxidative phosphorylation, occur in mitochondria.…”
Section: Introductionmentioning
confidence: 99%